2019
DOI: 10.18080/jtde.v7n1.181
|View full text |Cite
|
Sign up to set email alerts
|

A Threat Computation Model using a Markov Chain and Common Vulnerability Scoring System and its Application to Cloud Security

Abstract: Securing cyber infrastructures has become critical because they are increasingly exposed to attackers while accommodating a huge number of IoT devices and supporting numerous sophisticated emerging applications. Security metrics are essential for assessing the security risks and making effective decisions concerning system security. Many security metrics rely on mathematical models, but are mainly based on empirical data, qualitative methods, or compliance checking, and this renders the outcome far from satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The simulated results revealed that the architecture using the Markov model could be applied to achieve a flexible balance between network operating cost and MEC reliability. For computing the probability distribution of cloud security threats, a novel approach based on a Markov chain and common vulnerability scoring System was proposed in [29]. The approach allowed estimating the probabilities of cloud threats and types of attacks, which were confirmed by the simulation results.…”
Section: State Of the Artmentioning
confidence: 76%
See 1 more Smart Citation
“…The simulated results revealed that the architecture using the Markov model could be applied to achieve a flexible balance between network operating cost and MEC reliability. For computing the probability distribution of cloud security threats, a novel approach based on a Markov chain and common vulnerability scoring System was proposed in [29]. The approach allowed estimating the probabilities of cloud threats and types of attacks, which were confirmed by the simulation results.…”
Section: State Of the Artmentioning
confidence: 76%
“…The analyzed references considering Markov modelling for assessing the availability and cybersecurity of cloud and IoT systems can be divided into three groups: the references related to assessing availability and reliability [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], the references related to assessing cybersecurity [28][29][30][31][32][33][34][35][36][37][38][39], and references related to assessing both availability and cybersecurity as attributes of dependability of cloud and IoT systems [40][41][42][43].…”
Section: State Of the Artmentioning
confidence: 99%
“…Let us consider classification methods using the example in the paper [10]. The given table explains the relationship between threats and vulnerabilities as follows:…”
Section: Classification Example With Qanalysismentioning
confidence: 99%
“…The work in Reference 31 proposed a framework for detecting probabilities of compromising the network. Other recent works are also presented in References 32,33 . The presented model is based on dynamic analysis during the deployed phase of the network.…”
Section: Related Workmentioning
confidence: 99%